The power of informal institutions: The impact of clan culture on the depression of the elderly in rural China - Xiao-hong LIU; Wei-dong WANG; Lin-xiu ZHANG (Journal of Integrative Agriculture)
Exploration of ways to improve the subjective welfare of residents is an important area of current academic research. Using data from the China Family Panel Studies survey conducted in 2010, this paper investigated the impact of clan culture on the mental health of elderly people in rural China. The results demonstrated that clan culture can significantly decrease the depression score of the rural elderly. Further, there was no gender difference with respect to the impact of clan culture on the depression score of the elderly. At the same time, the positive effects of clan culture on the depression score of the elderly have gradually weakened with economic development. Exploration of the mechanisms involved indicated that in areas with stronger clan culture, older people receive more social support. This study enriches our understanding of the impact of informal institutions on the welfare of rural residents. At the same time, it can also provide a certain decision-making reference for the government to formulate relative poverty relief strategies in a new stage of poverty alleviation.